Keanekaragaman dan Kemelimpahan Jenis Anggrek (Orchidaceae) di Resort Selabintana Taman Nasional Gunung Gede Pangrango (TNGGP) Jawa Barat - Bela Prapitasari (Program Studi Pendidikan Biologi, FKIP Unpas,, 2020)
Gede Pangrango National Park (TNGGP) of West Java is one of the National Park that conserve orchid species. This study aims to determine what orchid species are found in Selabintana TNGGP, the most dominant orchid species found, determine the level of diversity of orchid species (H’), and determine the host tree used as epiphytic orchid habitat. The study was conducted at Selabintana TNGGP at two different location namely Cibereum Curug path and climbing path (altitude 1.500 asl). The data collection method is carried out using Visual Encounter Survey (VES) along the path with a radius to the right and left of one meter. The results found 46 types of orchids (25 epiphytic and 21 terestrial). The most dominant species found in the Curug Cibereum path is Erythrodes brevicalcar (137/ individual count 8.000 m2 ) and the most dominant species found in the climbing path is Liparis odorata (52 individual count/8.000 m2). The level of species diversity (H’) of orchids in Selabintana is classified as moderate ( Curug Cibereum path: 2,7; climbing path: 2,1). Host trees used as epiphytic orchid habitat are Schiima walici, Ficus sp, Cyathea sp, Dendronicde stimulans, and fellen branch. Keywords: Orchidaceae, Gede Pangrango National Park, Diversity, Host trees.